Exploring the use, perceptions, and challenges of mini-implants in orthodontic practice: a survey study - Panaite, Tinela; Balcos, Carina; Savin, Carmen; Olteanu, Nicolae Daniel; Karvelas, Nikolaos; Romanec, Cristian; Vieriu, Raluca-Maria; Chehab, Alice; Zetu, Irina (Frontiers in Oral Health, 2025)
The present study aims to explore and evaluate current practices among orthodontic specialists regarding the use of mini-implants, focusing on factors influencing usage decisions, experience in placement, perceptions of outcomes, and future perspectives of these devices in orthodontic practice. It seeks to explore the association between specialists' experience levels and their perceptions of mini implants, as well as the challenges encountered in their use. It is hypothesized that orthodontic specialists' perceptions and practices regarding the usage of mini implants are influenced by various factors, including their experience, training engagement, treatment outcomes, and preferences.Material and methodsThe study was conducted using an online, cross-sectional survey developed on the Survio platform to assess orthodontic specialists' perceptions of the clinical effectiveness and advantages of mini-implants in orthodontic treatments. The survey, consisting of 24 closed-ended questions in binary and multiple-choice formats, covered demographics, theoretical knowledge, clinical experience, and educational resources related to mini-implant use. Orthodontic specialists from Romania were invited to participate through the AREO association, and the survey was open for 12 weeks. Data collected from the survey were analyzed using descriptive statistics and multivariate logistic regression in SPSS software (Version 28), with a statistical significance threshold set at p < 0.05.Resultsthrough a comprehensive analysis of survey data, the study investigates factors influencing specialists' perceptions, challenges encountered in practice, training engagement, material preferences, treatment outcomes, and indications for mini-implant usage. Notable correlations and discrepancies between documented literature and orthodontists' responses in Romania regarding mini-implant indications are explored, shedding light on the diversity of applications in orthodontic procedures highlighting the significance of education, training, and technical support in enhancing mini-implant utilization. Strategies to address barriers and promote informed decision-making among orthodontists are discussed.Conclusionsthe study reveals diverse preferences and utilization patterns regarding mini-implants across different orthodontic procedures, reflecting the versatility and adaptability of these devices in addressing various clinical needs. By comparing documented literature with real-world practices, the study identifies both correlations and discrepancies, providing valuable insights into the practical application of mini-implants in orthodontic treatments.